Can Aspirin Minimize Stroke Risk and New Lesion Formation in Multiple Sclerosis? - Avasarala, Jagannadha; Parti, Naveen (Frontiers in Neurology, 2018)
Even with increasing data implicating the venous side of the vascular tree of the brain in MS, no diagnostic or treatment protocol has addressed the risk of acute stroke in MS and no systematic study has documented the incidence or prevalence of acute stroke in MS patients. Approximately 795,000 strokes occur in the U.S. each year - every 40 seconds, someone has a stroke and every 4 minutes, a person dies from a stroke. However, no large, prospective, multi-center study has investigated acute stroke incidence in MS patients either in the U.S. or internationally, leaving a gap in our understanding of the association between stroke and MS. Additionally, data on acute stroke in MS as determined by age, gender or ethnicity are unknown. To compound this further, the diagnosis and definition of acute stroke in MS remains poorly understood. A survey of published literature shows a few anecdotal reports of acute stroke occurring among MS patients, but most studies do not address the fundamental association between acute stroke and MS. Symptoms of acute stroke and MS can overlap and the lack of clear clinical/radiological criteria that alert the patient or clinician to the development of acute stroke in an MS patient compound the dilemma, even leading to the administration of IV altelpase in cases that are later diagnosed as either MS or having an 'MS flare'. Clinical trials that use aspirin in multiple sclerosis are urgently needed.